EFL TEACHERS’ DEMANDS AND PREFERENCES ON IN-SERVICE TRAINING IN TURKEY - Önalan, Okan; Gürsoy, Esim (International Online Journal of Education and Teaching, 2020)
One of the significant means of ensuring quality instruction in language classrooms is establishing an effective program of continuing professional development for language teachers. When conducted efficiently as a part of CPD, in-service training (INSET) proves to be a key component in improving teachers’ instructional skills as well as keeping their methodological knowledge up-to-date. Nonetheless, both state-led and private-held INSET efforts in Turkey receive considerable criticism regarding their inefficiency and insufficiency. One of the reasons for any ineffectiveness might be INSET program developers’ negligence in taking into consideration teachers’ actual needs. Thus, more empirical research that explores language teachers’ demands and preferences on in-service training should be carried out in various contexts. Consequently, this study aims to investigate English teachers’ demands and preferences on an INSET program. Descriptive in nature and following a quantitative research design, the present study collected data from 985 state and private school teachers via a scale developed by the researchers. Having ensured construct validity via factor analysis, the scale consisted of three sub-factorial groups: demands on INSET, preferences regarding the content and the trainers, and personal preferences. The findings displayed some statistically significant differences between state and private schools, novice and experienced teachers, and between teachers who had previous INSET experience and those who do not at different sub-factorial groups. The study has implications for policymakers, who are in the process of designing an INSET model for Foreign Language Teachers, as well as teacher trainers who carry out INSET.